Pasatiempo de los estudiantes de una academia en la región Huancavelica: un análisis preliminar - Quispe Mendoza, Mariluz (2023)
The objective of this research work is to demonstrate the various discriminating and similar activities carried out by young fifth-year high school students from an academy located in the Huancavelica region in their free time, their degree of participation in society as adolescents and students at doors of completing secondary education and how many consumers are of technology in this digital age (expansion of the web) such as: social networks, virtual games, online communication, etc. This research used the ethnographic method of descriptive level and to collect information. An interview was applied. Sampling was intentional and for accessibility. The results evidenced the different hobbies, as well as highlighting the similarity between many of them, such as spending their “free time” alone; as well as having as a key objective in the short term how to obtain a vacancy to continue university studies.